Species diversity and spatial pattern of urban ancient trees in biodiverse Southwest China - Wei, Lijuan; Wang, Guohai; Li, Xiaoying; Zhang, Huangmin; Yang, Jingjun; Pan, Liqin; Jim, Chi Yung (Frontiers in Ecology and Evolution, 2026)
IntroductionAncient trees are keystone ecological and cultural entities ancient that provide essential services to humans in settlements. The unique natural and cultural geography in the China-Vietnam border region provides relatively undisturbed habitats for ancient trees. Cross-border activities, policy disparities, and uneven conservation resources currently challenge their survival and diversity.MethodsA study was conducted in Chongzuo city, a typical border city, to quantify the species diversity, abundance and distribution of ancient trees, and their relationship with varied habitats. Redundancy analysis (RDA) identified the primary factors influencing their spatial patterns.ResultsThe results identified 15,722 ancient trees from 99 species, 73 genera and 35 families. Twenty-nine species were solitary with only one individual each, and 14 were listed as protected plants in China. The population was dominated by Camellia drupifera, Ficus altissima, Dimocarpus longan, and Excentrodendron tonkinense, collectively accounting for 84.05% of the recorded trees. Ancient trees decreased with tree age, height, DBH, and crown width, with the majority (95.33%) in the 100–299 years age group. More natural habitats, including mountains, villages, and farmlands, supported the highest trees abundance, while parks, nature reserves, and scenic spots accommodated the greatest species richness. Pingxiang township had the highest tree abundance (9,118), while Longzhou had the highest species richness (50). Ningming, however, had the largest Shannon-Wiener index (H = 2.42), making it the most important district for preserving tree diversity. Land area, built-up area, GDP, population density, forest coverage, farmland area, and altitude significantly influenced the distribution of ancient trees.DiscussionThe inherently high landform and habitat diversities in the study area support many ancient tree species. Due to the complex terrain, in-depth, long-term, and systematic research remains relatively scarce. Future studies could integrate natural and anthropogenic factors to explore the survival patterns and conservation needs, allowing the formulation of targeted strategies for their sustainable protection.